THE EXISTENCE OF INDIE BAND GROUP FRIEND OVER YOU IN KEDIRI - Denis Arditya Putra (Universitas Negeri Surabaya, 2020)
The indie band Kediri varies, which is developing at this time one of them that has a pop genre is Friend Over You. The research problem formulation is (1) How is the background of the formation of Friend Over You? (2) How is Friend Over You developing? (3) What is the effort of Friend Over You in maintaining its presence in the community?. This research use desciptive qualitative approach. Data collection techniques used observation, interviews, and document studies. The results of this study: (1) Friend Over You was formed on December 13, 2013 in the form of rock formed by Achild and Riko. (2) Friend Over You works according to the times, thus changing the genre to pop. (3) Friend Over You maintains its existence by having a music label and participating in the Yowis Ben 2 Movie Promo Tour in several Cities throughout East Java.